The Income and Food Sufficiency Level of Participant and Non Participant Families of PDM-DKE Program In Bogor, West Java 1998/1999 - . Novita; Cesilia M Dwiriani; M Rizal M; . Damanik (Media Gizi dan Keluarga, 2000)
The objective of this study is to analyze family’s income and food sufficiency level. The total samples of 180 families were randomly selected, where 115 samples were the participant and 65 samples were non-participant families of PDM-DKE program in Bogor. The study was conducted in four-district areas (kelurahan) in Bogor City (kotamadya). Data analysis consists of descriptive and inferential statistics, such as Mann Whitney for difference’s test and Rank Spearman for correlation test. The results showed that family’s income and food sufficiency level were not significantly different between the two groups. The average income of participant families was Rp105.700 and the average income of non-participant families was Rp104.400. The sufficiency level of vitamin A at non-participant families is considered deficient (50%). The size of the family is negatively correlated with food sufficiency level of the two group sample families, while family’s income is positively correlated with food sufficiency level of the participant families. Housewives educational level and nutrition knowledge was tent to effect the food sufficiency level of the sample families.Keywords: food sufficientcy, income